Effects of Educational Mistmatch on Wages in the Korean Labor Market*. Issue 4 (December 2016) - Lee, Hanol; Lee, Jong‐Wha; Song, Eunbi
Abstract : Using data on Korean workers from the Programme for the International Assessment of Adult Competencies, the present study empirically investigates the incidence and wage effects of educational mismatch. Among full‐time workers aged 25–54, approximately 27 percent are overeducated and 15 percent are undereducated. Our results reveal that, after controlling for omitted variable bias and measurement errors, return to an additional year of overeducation is significantly less than that to a year of required education, whereas undereducated workers do not appear to suffer wage penalties associated with their deficit schooling. The findings also show that returns to a year of overeducation vary across fields of study. The returns to overeducation for college graduates from health and welfare, engineering and manufacturing, and social sciences, business and law are relatively high compared with those in agriculture, services, and humanities and arts.